The Impact of The Russia-Ukraine War on The Dynamics of The Asean-5 Stock Market - Agung, Damar; Ermawati, Wita Juwita; Suprayitno, Gendut (Eduvest - Journal of Universal Studies, 2023)
The capital market can be defined as activities related to public offerings, securities trading, public companies, institutions, and certain professions. One of the factors considered in stock investment is the Efficient Market Hypothesis. The Efficient Market Hypothesis is a financial theory that discusses how asset prices in the market already reflect all available information. This study employs an approach to detect market reaction and market efficiency based on the event of the world oil price decline due to the Russian invasion of Ukraine on March 10, 2022, through excess or abnormal return, price impact, and fluctuation patterns observed using a multifractal model. The research results on the abnormal return of the ASEAN-5 stock index showed a significant negative reaction at t-5 and t-3 during the event of the world oil price decline due to the Ukraine and Russia war in 2022 and a significant positive reaction at t-0 during the event. The average abnormal return before and after the announcement of the world oil price decline due to the Ukraine and Russia war in 2022 showed a significant negative reaction, but there was no significant difference in price impact between before and after the event. The efficiency level of the stock index in ASEAN-5 did not show a significant difference after the announcement of the world oil price decline due to the Ukraine and Russia war in 2022.